2011
DOI: 10.1111/j.1365-2702.2010.03484.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of randomised controlled trials of the effects of warmed irrigation fluid on core body temperature during endoscopic surgeries

Abstract: Warming irrigating fluid should be considered standard practice in all endoscopic surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 32 publications
0
20
0
4
Order By: Relevance
“…Administration of excessive amounts of irrigation fluids may contribute to heat loss. Studies of surgical procedures in which irrigation fluids are administered have produced conflicting results regarding whether irrigation fluids increase the risk of hypothermia [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of excessive amounts of irrigation fluids may contribute to heat loss. Studies of surgical procedures in which irrigation fluids are administered have produced conflicting results regarding whether irrigation fluids increase the risk of hypothermia [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There are a series of complications and adverse effects related to hypothermia; i.e., cardiac arrhythmias and ischemia, reduced drug metabolism, late emergence and late recovery from anesthesia, mental state changes, impaired renal function, impaired wound healing, elevated infection rates, bleeding disorders, shivering, elevated oxygen consumption, impaired peripheral circulation, hypercarbia, hypoxia, and lactic acidosis [1][2][3][4][5]. Because of these critical complications, all necessary precautions should be considered and meticulously applied when appropriate to avoid hypothermia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Жидкости для интраоперационной иррига-ции должны быть предварительно подогре-ты до 38-40 °С [41]. Особые группы пациентов: дети.…”
unclassified
“…A systematic review recently reported that circulating water garments offered more effective temperature control than forced-air warming systems, and that both were better for temperature control than passive warming devices [5]. Another systematic review reported that the use of room temperature irrigation fluid led to greater decreases in core body temperature and increased the risk of perioperative hypothermia and shivering compared with warmed irrigation fluid [6]. An alternative technique is to promote the patients' own ability to generate heat by the infusion of amino acids, which are known to be effective at enhancing thermogenic effects and alleviating shivering during the perioperative period [7].…”
Section: Introduction Of Perioperative Hypothermiamentioning
confidence: 99%